Overexpression of lymphotoxin in T cells induces fulminant thymic involution. - Heikenwalder, M; Prinz, M; Zeller, N; Lang, K; Junt, T; Rossi, S; Tumanov, A; Schmidt, H; Priller, J; Flatz, L; Rülicke, T; Macpherson, A; et al. (2008)
Activated lymphocytes and lymphoid-tissue inducer cells express lymphotoxins (LTs), which are essential for the organogenesis and maintenance of lymphoreticular microenvironments. Here we describe that T-cell-restricted overexpression of LT induces fulminant thymic involution. This phenotype was prevented by ablation of the LT receptors tumor necrosis factor receptor (TNFR) 1 or LT beta receptor (LTbetaR), representing two non-redundant pathways. Multiple lines of transgenic Ltalphabeta and Ltalpha mice show such a phenotype, which was not observed on overexpression of LTbeta alone. Reciprocal bone marrow transfers between LT-overexpressing and receptor-ablated mice show that involution was not due to a T cell-autonomous defect but was triggered by TNFR1 and LTbetaR signaling to radioresistant stromal cells. Thymic involution was partially prevented by the removal of one allele of LTbetaR but not of TNFR1, establishing a hierarchy in these signaling events. Infection with the lymphocytic choriomeningitis virus triggered a similar thymic pathology in wt, but not in Tnfr1(-/-) mice. These mice displayed elevated TNFalpha in both thymus and plasma, as well as increased LTs on both CD8(+) and CD4(-)CD8(-) thymocytes. These findings suggest that enhanced T cell-derived LT expression helps to control the physiological size of the thymic stroma and accelerates its involution via TNFR1/LTbetaR signaling in pathological conditions and possibly also in normal aging.